Antynomia życia i śmierci w poezji Inny Lisnianskiej - Letka-Spychała, Olga (Acta Polono-Ruthenica, 2010)
The article explores life and death antinomy in the Inna Lisnyanskayas poetry. The subject of this analysis is the series of poems Archivy published in 2006 in the magazine Druzhba Narodov. Characteristic element of the Lisnyanskayas poems is an archive which can be regarded as a main leitmotif. In the article particular attention has been paid to conceptual metaphors: DEATH IS AN ARCHIVIST, ARCHIVE IS HELL, LIFE IS AN ARCHIVE. The study is an attempt at cognitive analysis of the life and death antinomy.